Effect of Clamping Rigidity of the Armour on Ballistic Performance - Dikshit, S. N.; Sundararajan, G. (Defence Science Journal, 2013)
Influence of the manner in which the armour plates are held during their ballistic testing on the armour performance, has been evaluated. One armour plate was clamped rigidly to the test stand while a second plate of identical composition, hardness, and dimensions was hung loosely from the target holder. Both these plates were impacted with the same type of projectiles and over the same impact velocity range. The nature of ballistic damage evaluated indicates that the manner in which the armour is held during ballistic testing has a negligible influence on its performance at least when the mass of the plate is substantially higher than that of the projectile.